2013
DOI: 10.1371/journal.pone.0067353
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Biomass, Basal Respiration and Enzyme Activity of Main Forest Types in the Qinling Mountains

Abstract: Different forest types exert essential impacts on soil physical-chemical characteristics by dominant tree species producing diverse litters and root exudates, thereby further regulating size and activity of soil microbial communities. However, the study accuracy is usually restricted by differences in climate, soil type and forest age. Our objective is to precisely quantify soil microbial biomass, basal respiration and enzyme activity of five natural secondary forest (NSF) types with the same stand age and soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 58 publications
9
62
1
3
Order By: Relevance
“…Non-cultivated soils, dominating in urban areas, contain more organic carbon because roots play a disproportionately important role in the carbon budget in soils (Mazilli et al 2015). Furthermore, soil organic carbon mineralization is affected by soil aggregation (Fazzle Rabbi et al 2014;Jia et al 2015), while physicochemical features of the soil influence the microbial properties (Cheng et al 2013). You et al (2014) demonstrated the complex interactions and linkage among plant traits, microenvironment, and soil physiochemical properties, which affect soil organic carbon via microbial regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Non-cultivated soils, dominating in urban areas, contain more organic carbon because roots play a disproportionately important role in the carbon budget in soils (Mazilli et al 2015). Furthermore, soil organic carbon mineralization is affected by soil aggregation (Fazzle Rabbi et al 2014;Jia et al 2015), while physicochemical features of the soil influence the microbial properties (Cheng et al 2013). You et al (2014) demonstrated the complex interactions and linkage among plant traits, microenvironment, and soil physiochemical properties, which affect soil organic carbon via microbial regulations.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the activity of some enzymes (e.g. hydrolytic, proteolytic, laccases, cellulases, phosphatase) has been reported in soils irrigated with treated wastewater (Adrover et al, 2012;Alguacil et al, 2012;Chevremont et al, 2013;Elifantz et al, 2011;Frenk et al, 2014;Friedel et al, 2000;Meli et al, 2002;Morugán-Coronado et al, 2013). It is, thus, suggested that wastewater irrigation may stimulate the activity of microorganisms involved in the biochemical balance of elements such as C, N and P. In addition, organic matter may stabilize the enzymes, which remain active in the ex-tracellular medium, independently of the soil microbial (Trasar-Cepeda et al, 2008a).…”
Section: Effects On Microbial Abundance and Activitymentioning
confidence: 94%
“…The influence of organic matter supply on the microbiota is suggested by the fact that wastewater irrigation was sometimes associated with an increase in soil microbial biomass and in soil enzyme activities (Table 4). Examples are the activities of enzymes such as dehydrogenase, laccase, cellulase, protease and urease (Chevremont et al, 2013;Friedel et al, 2000;Liu and Haynes, 2011;Morugán-Coronado et al, 2013). These effects are probably due to the stimulation of microbial growth and activity, boosted by the organic matter and nutrients supplied by wastewater (Adrover et al, 2012;Chevremont et al, 2013;Friedel et al, 2000;Liu and Haynes, 2011;Morugán-Coronado et al, 2013;Tam, 1998).…”
Section: Organic Mattermentioning
confidence: 99%
“…Because soil microorganisms are very sensitive to their environment, changes in soil composition result in rapid alterations in soil microbial species [11]. Owing to their value for ecosystem functional assessment, soil microbial indices have been used for monitoring soil quality [12]. Some research has shown that the distribution of soil microorganisms is closely associated with soil environmental conditions, soil physicochemical factors, plant communities, and other factors that all change during ecosystem development [13][14].…”
Section: Introductionmentioning
confidence: 99%